2011
DOI: 10.1002/ajh.22091
|View full text |Cite
|
Sign up to set email alerts
|

Systemic infections mimicking thrombotic thrombocytopenic purpura

Abstract: The absence of specific diagnostic criteria, the urgency to begin plasma exchange treatment, and the risk for complications from plasma exchange make the initial evaluation of patients with suspected thrombotic thrombocytopenic purpura (TTP) difficult. Systemic infections may mimic the presenting clinical features of TTP. In the Oklahoma TTP-HUS (hemolytic-uremic syndrome) Registry, 1989–2010, 415 consecutive patients have been clinically diagnosed with their first episode of TTP; in 31 (7%) the presenting cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 84 publications
(79 reference statements)
0
89
0
Order By: Relevance
“…For example, RMSF-associated cutaneous necrosis and gangrene might be difficult to distinguish clinically from purpura fulminans associated with meningococcemia (105). RMSF-associated neurologic manifestations, renal failure, and thrombocytopenia have led to confusion with the diagnosis of thrombotic thrombocytopenic purpura (TTP) (106)(107)(108). RMSF-associated vasculitis has been confused with idiopathic, acute vasculitides, such as Kawasaki disease in pediatric patients.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…For example, RMSF-associated cutaneous necrosis and gangrene might be difficult to distinguish clinically from purpura fulminans associated with meningococcemia (105). RMSF-associated neurologic manifestations, renal failure, and thrombocytopenia have led to confusion with the diagnosis of thrombotic thrombocytopenic purpura (TTP) (106)(107)(108). RMSF-associated vasculitis has been confused with idiopathic, acute vasculitides, such as Kawasaki disease in pediatric patients.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…It is also associated with thrombocytopenia (i.e., TCIP) and disseminated intravascular microthrombosis (DIT) [28,29]. Other clinical syndromes associated with critical illnesses include SIRS [13,14], ARDS [19,22], MODS [4,6,11,12,14], "DIC" [30][31][32], thrombotic thrombocytopenic purpura (TTP)-like syndrome [33][34][35][36][37][38][39], hepatic coagulopathy, and others [36,40].…”
Section: Endothelium and Critical Illnessesmentioning
confidence: 99%
“…Both almost always occur in critical illnesses (e.g. sepsis/ septic shock, trauma, immunologic and collagen-vascular diseases, and complications of surgery, pregnancy and transplant) [38,60,61]. Pathologically both are characterized by arteriolar and capillary hyaline microthrombi with variable fibroblastic proliferation [49,62].…”
Section: Endotheliopathy-associated Vascular Microthrombotic Diseasementioning
confidence: 99%
“…Clinical studies have demonstrated that thalidomide and lenalidomide each have their own distinct toxicity and efficacy [1][2][3][4] despite sharing an overlapping immunomodulatory profile [5,6]. It is evident that patients previously refractory to the less potent IMiD thalidomide can still respond when treated with lenalidomide [7,8].…”
mentioning
confidence: 99%
“…In their recent article, Booth et al describe a number of cases of systemic infection with reduced a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) activity, whose presenting clinical features mimicked thrombotic thrombocytopenic purpura (TTP) [1]. In the past, a small number of cases of leptospirosis have been reported to be associated with TTP [2][3][4].…”
mentioning
confidence: 99%